The influence of calcium–magnesium–aluminosilicate deposits on internal stresses in Yb2Si2O7 multilayer environmental barrier coatings. (15th February 2016) - Stolzenburg, F.; Kenesei, P.; Almer, J.; Lee, K.N.; Johnson, M.T.; Faber, K.T.
Abstract: The interaction of calcium-magnesium-aluminosilicates (CMAS) with Yb2 Si2 O7 -based multilayer environmental barrier coatings was studied using a combination of high-energy synchrotron X-ray techniques. Changes in the phase-specific stresses and lattice spacings as a function of temperature were investigated with wide-angle X-ray scattering. Small-angle X-ray scattering was used to study the interaction of CMAS with nanoporosity, while X-ray computed tomography was used to study the formation of cracks in the coating. It was found that CMAS interacts strongly with the Yb2 Si2 O7 topcoat, leading to changes in lattice spacing, alterations of the ambient temperature stresses, and large cracks in the CMAS that extend through the topcoat. Graphical abstract: